Screening and characterization of methane producing bacteria from sago waste - Dahalia, anak Jerim (Universiti Malaysia Sarawak (UNIMAS), 2012)
A study was done to determine the presence of methane producing bacteria, methanogens, in sago wastes. The bacteria was cultured in sealed bottles containing Luria broth and the sago wastes. One of the bottles was incubated at 30°C and the other one at room temperature. The bacteria were then inoculated and culutured in LB agar plates for several days. The growth of bacteria was being observed. The bacteria colonies have white colonies. Through staining, the bacteria was Gram positive bacteria and microscopic observation determined the characteristic of the bacteria showed to be rod shaped. Further study was done by using DNA extraction to determine the presence of 16S ribosomal bacteria. The sample from bacteria incubated in 30°C temperature showed the appearance of bands during AGE. After running the AGE, the template from extraction was used for PCR processes. The primer ME1, ME2, mmox f, mmox r, 27, 1525, mb 1007, mc 1005, mm 1007 and ms 1020 were used as forward and reverse primers during PCR processes. The AGE process of PCR products showed the appearanced of bands in the primer samples except in sample with primer mmoX. After the PCR process, the samples were sent to 1st Base Sequencing Company for direct sequencing.